Effects of Calcination Temperature on Preparation of Boron-Doped TiO2 by Sol-Gel Method - Wenjie Zhang; Bo Yang; Jinlei Chen (International Journal of Photoenergy)
Boron-doped TiO2 photocatalyst was prepared by a modified sol-gel method. Being calcinated at temperatures from 300°C to 600°C, all the 3% B-TiO2 samples presented anatase TiO2 phase, and TiO2 crystallite sizes were calculated to be 7.6, 10.3, 13.6, and 27.3 nm, respectively. The samples were composed of irregular particles with rough surfaces in the size range within 3 μm. Ti atoms were in an octahedron skeleton and existed mainly in the form of Ti4+, while the Ti-O-B structure was the main boron existing form in the 3% B-TiO2 sample. When calcination temperature increased from 300°C to 600°C, specific surface area decreased sharply from 205.6 m2/g to 31.8 m2/g. The average pore diameter was 10.53 nm with accumulative pore volume of 0.244 mL/g for the 3% B-TiO2 sample calcinated at 400°C, which performed optimal photocatalytic degradation activity. After 90 min of UV-light irradiation, degradation rate of methyl orange was 96.7% on the optimized photocatalyst.